Reliability of Zagreb 82 MOD Cephalometric Assessment in Determining the Facial Growth Pattern - Ivana Parčina Amižić; Luka Šimunović; Marina Lapter Varga (Acta Stomatologica Croatica)
Objective: The aim of this study was to investigate accuracy and reliability of the existing cephalometric analysis Zagreb82 MOD in determining the facial growth pattern. Materials and methods: Of all patients aged 10-17 years without missing teeth, craniofacial anomalies and previous orthodontic medical history, who were attending Department of Orthodontics, University Hospital Centre Zagreb in years 2021 and 2022, lateral cephalograms and digital dental models were examined. Subsequently, subjects were collected and divided into two groups: eugnathic group (N=50, SNA 81°±3.5°, SNB 78.5°±3°, ANB 2.5°±2°, Wits -1±2mm, Angle class. I, overbite 1-3.5mm, overjet 1-3.5mm, dystopia<3mm, total crowding<3mm, total diastemas<3mm) and test group (N=129, overbite>4mm for deep bite and overbite<-0.1mm for open bite). In the eugnathic group, reference values were calculated for ten skeletal parameters and a corrected analysis was created. In the test group, facial growth patterns (horizontal, neutral or vertical) were determined, within the corrected and Zagreb82 MOD analysis. The T-test was used to examine the differences between the corrected and the Zagreb82 MOD analysis. The McNemar test was performed to compare the distribution of facial growth patterns between the tested parameters within and between analyses. Results: Differences were observed in the reference values of saddle angle, Y-axis, articular angle, mandibular angle, Björk’s Sum and upper section of mandibular angle (p<.05). The distribution of facial growth patterns according to Y-axis, intermaxillary angle, mandibular angle, Bjork’s Sum also differed between the two analyzes (p<.001). In the corrected analysis, there was no significant difference in the distribution of facial growth patterns between Björk’s Sum, mandibular inclination, and intermaxillary angle (p>.05). Conclusion: The reliability of Zagreb82 MOD analysis in defining facial growth pattern should be taken with caution. Björk’s Sum, intermaxillary angle and inclination of mandible are equitable parameters in determining the facial growth pattern within the corrected analysis.